2019
DOI: 10.20448/journal.522.2019.51.93.96
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Positivity and Fear of Happiness in People Applying to Graduate Programs in Physical Education and Sports Department

Abstract: Positivity is a positive concept for both students and teachers and academics. This people' perspectives are influencing many factors. For this reason, a positive point of view is also an important factor. This perspective affects many negative situations. One of these situations is fear of happiness. The aim of the study with this thought is to examine the relationship between positivity and fear of happiness in people applying to the graduate programs of Physical Education and Sports Department. Study sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…The “full-practice” concept and its teaching methods are scientific and feasible forms of teacher education. It can infiltrate practical teaching throughout the learning process of undergraduates, which is consistent with the current development trend of practical talent cultivation ( Togo and Caz, 2019 ). Recently, with the increasing development of education in China, national policies have also greatly supported the talent cultivation of undergraduates majoring in early childhood education.…”
Section: Methodssupporting
confidence: 74%
“…The “full-practice” concept and its teaching methods are scientific and feasible forms of teacher education. It can infiltrate practical teaching throughout the learning process of undergraduates, which is consistent with the current development trend of practical talent cultivation ( Togo and Caz, 2019 ). Recently, with the increasing development of education in China, national policies have also greatly supported the talent cultivation of undergraduates majoring in early childhood education.…”
Section: Methodssupporting
confidence: 74%
“…On the other hand, there are also results in which women's fear of happiness levels are higher than men's (Tekke and Özer 2019). There are also studies that do not find any relationship regarding gender (Togo and Caz 2019, Özen 2019, Eksi et al 2020.…”
Section: Discussionmentioning
confidence: 98%
“…This fear can be thought of as a belief about experiencing a situation that will cause sadness immediately after excessive joy. As a matter of fact, when different definitions are examined, the fear of happiness is basically the belief that the state of happiness may be a harbinger of bad situations that will follow (Gilbert et al 2012, Joshanloo 2013, Sarı and Çakır 2016, Togo and Caz 2019. People who are afraid of happiness can get less satisfaction in their lives (Joshanloo 2013, Yıldırım and Aziz 2017, Esin Gulel and Çağlar 2019, Tekke and Özer 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Joshanloo (2013) found that there was a significant negative correlation between the scores obtained for the fear of happiness variable and the scores of life satisfaction and well-being. Togo et al (2019) discussed the relationship between being positive and fear of happiness in postgraduate students in physical education and sports. A moderately negative relationship was found between being positive and fear of happiness.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on fear of happiness, fear of happiness is associated with the concepts of life satisfaction, psychological well-being, subjective well-being, hopefulness, psychological resilience, happiness, well-being and emotional intelligence. In these studies, fear of happiness is negatively correlated with positive emotions at different levels (Baş et al, 2021;Elmas, 2021;Joshanloo, 2013;Muhtar, 2016;Özkan, 2020;Sarı et al, 2016;Tekke et al, 2019;Togo et al, 2019;Yıldırım, 2019). In addition, the relationship between the fear of happiness, age and gender, as demographic characteristics, was investigated (Gilbert et al, 2012;Özkan, 2020;Şar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%